Evaluating match running performance in elite Australian football: a narrative review - Christopher Wing; Nicolas H. Hart; Fadi Ma'ayah; Kazunori Nosaka (BMC, 2021)
Abstract During Australian football (AF) matches, players are subjected to high running loads, which are intermittent in nature. There is a growing body of research that highlights factors which can both positively and negatively affect this match running performance (e.g., the total distance travelled by a player during match-play). In order to appropriately evaluate these factors, a thorough search of MEDLINE, SportDiscus and Web of Science databases was performed, with a total of 17 manuscripts included within the final evaluation. The main findings from this review highlighted that match running performance is increased amongst those playing in midfield and half back/forward positions, in players with lower playing experience, as well as in matches against higher quality opponents, and in losing quarters. Additionally, a well-design interchange-rotation strategy may be able to positively affect match running performance. A decrease in match running performance was evident amongst more experienced players, during periods of acute fatigue (e.g., following periods of high intensity activity), during matches played in higher temperatures and matches with an increased number of stoppages. However, no effect of ground hardness or size, as well as responses to self-reported wellness questionnaires was found. Other factors such as finals series matches, pre-season training load and elements related to the schedule have been shown to have substantial conflicting results within the literature, increasing the difficulty in making generalisable conclusions to their effect on match running performance. Developing a thorough understanding of these factors which affect match running performance can aid practitioners and coaches to gain a greater understanding of a player's performance as well as inform the development of strategies for its improvement.